2016
DOI: 10.1590/1678-775720150560
|View full text |Cite
|
Sign up to set email alerts
|

Fifty years of Brazilian Dental Materials Group: scientific contributions of dental materials field evaluated by systematic review

Abstract: Objective A systematic review was conducted to analyze Brazilian scientific and technological production related to the dental materials field over the past 50 years.Material and Methods This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (Prisma) statement. Searches were performed until December 2014 in six databases: MedLine (PubMed), Scopus, LILACS, IBECS, BBO, and the Cochrane Library. Additionally, the Brazilian patent database (INPI - Instituto Nacional de Proprieda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…The three main subjects addressed in articles were dental materials (21.6%), endodontics (19.3%), and oral pathology/stomatology (13.1%), which is in line with data shown in Figure 1. In addition, it has been shown that Brazil is a great contributor to the international dental materials science output, with a substantial number of articles and patents published yearly (4). Interestingly, the presence of funding text was not high in the sample, only 1.4% of articles, with an average 1.4 cites/doc.…”
Section: Resultsmentioning
confidence: 88%
“…The three main subjects addressed in articles were dental materials (21.6%), endodontics (19.3%), and oral pathology/stomatology (13.1%), which is in line with data shown in Figure 1. In addition, it has been shown that Brazil is a great contributor to the international dental materials science output, with a substantial number of articles and patents published yearly (4). Interestingly, the presence of funding text was not high in the sample, only 1.4% of articles, with an average 1.4 cites/doc.…”
Section: Resultsmentioning
confidence: 88%
“…Studies in implantology in Brazil have been increasing, and dental materials had the highest number of published articles up until 2016 (13,708 articles). Nevertheless, the amount of patents is modest, as the process for a product to be patented is complex and the number of depositories is not proportional to the number of scientific studies in the area (Rosa et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Studies indicate that the Brazilian dental industry used to focus on the production of restorative materials; however, the current trends are investments in technology, because there is a concern to improve the development of biomaterials (Rosa et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Foi identificado que os quatro primeiros autores (Quadro 2) que mais publicaram na área trabalham com pesquisas voltadas aos materiais dentários, sendo o Brasil referência mundial no desenvolvimento tecnológico e científico desse campo (ROSA et al, 2016).…”
Section: Posição Autor Instituição Nº De Publicaçõesunclassified
“…Ao analisar os títulos do CiteScore (Quadro 6) com os da Tabela 2, três periódicos não constam nesta última: Periodontology 2000, Oral Oncology e o Molecular Oral Microbiology.Observa-se ainda na Tabela 5 que o periódico Dental Materials aparece na primeira posição com o maior índice h e em segundo lugar em número de citações recebidas, além de estar entre as maiores classificações nos indicadores de fator de impacto e CiteScore (Quadro 5 e 6), o que representa ser um dos mais importantes periódicos internacionais na área de odontologia. Trata-se de um periódico pertencente à editora Elsevier, com modelo de publicação híbrido e com foco nas propriedades ou no desempenho de materiais dentários.SegundoRosa et al (2016), a ciência dos materiais dentários, além de avaliar os materiais, se preocupa com o desenvolvimento de novos e melhores produtos. Os autores verificaram que as produções científicas e tecnológicas brasileiras nesse campo foram identificadas em diferentes especialidades da odontologia, com significativa representação e reconhecimento mundial.…”
unclassified